2011
DOI: 10.1017/s1751731111000589
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the requirement of dietary crude protein for growing blue-breasted quail (Excalfactoria chinensis)

Abstract: Two experiments were conducted to investigate the requirement for dietary crude protein (CP) in growing blue-breasted quail (BBQ). In Experiment 1, 300 1-day-old quails were randomly assigned to 10 groups according to a 2 3 5 factorial arrangement of treatments with two metabolisable energy (ME) levels (12.13 and 13.39 MJ/kg) and five CP concentrations (160, 190, 220, 250 and 280 g/kg) for 8 weeks. In Experiment 2, 300 1-day-old quails were subjected to a different factorial arrangement of treatments with tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…An interaction existed in weight gain between energy and protein as least weight gain (P<0.05) observed in both ME (12.13 and 13.39) fed groups with low CP diet [26]. Significantly (P<0.01) higher gain in weight and better FCR was observed by supplementing highest level of protein and energy combination (27% CP with 3200 Kcal ME/kg) [13,27].…”
Section: Experimental Designmentioning
confidence: 99%
“…An interaction existed in weight gain between energy and protein as least weight gain (P<0.05) observed in both ME (12.13 and 13.39) fed groups with low CP diet [26]. Significantly (P<0.01) higher gain in weight and better FCR was observed by supplementing highest level of protein and energy combination (27% CP with 3200 Kcal ME/kg) [13,27].…”
Section: Experimental Designmentioning
confidence: 99%
“…A level of P , 0.05 was used as the criterion for statistical significance. The one-slope quadratic broken-line model used to determine the individual protein requirements for maintenance and growth (Morris, 1999;Robbins et al, 2006) was similar to those reported by Wei et al (2011).…”
Section: Statistical Analysesmentioning
confidence: 81%
“…By the end of the experiment, it was possible to determine the sex by appearance and there were only 88 females and 84 males because eight birds died during the trial period. The temperature in each brooder was maintained at 40 6 18C for the first 2 weeks and was subsequently decreased by 28C every 2 days to 308C (Wei et al, 2011). The birds received for 2 weeks ad libitum water and a diet with a metabolisable energy concentration of 12.13 MJ/kg and a dietary CP concentration of 125,150,175,200,225 or 250 g/kg (Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations